Neuroinflammatory Gene Regulation, Mitochondrial Function, Oxidative Stress, and Brain Lipid Modifications With Disease Progression in Tau P301S Transgenic Mice as a Model of Frontotemporal Lobar Degeneration-Tau. Issue 10 (October 2015) - López-González, Irene; Aso, Ester; Carmona, Margarita; Armand-Ugon, Mercedes; Blanco, Rosi; Naudí, Alba; Cabré, Rosanna; Portero-Otin, Manuel; Pamplona, Reinald; Ferrer, Isidre
Abstract : Abstract: Tau P301S transgenic mice (PS19 line) are used as a model of frontotemporal lobar degeneration (FTLD)-tau. Behavioral alterations in these mice begin at approximately 4 months of age. We analyzed molecular changes related to disease progression in these mice. Hyperphosphorylated 4Rtau increased in neurons from 1 month of age in entorhinal and piriform cortices to the neocortex and other regions. A small percentage of neurons developed an abnormal tau conformation, tau truncation, and ubiquitination only at 9/10 months of age. Astrocytosis, microgliosis, and increased inflammatory cytokine and immune mediator expression also occurred at this late stage; hippocampi were the most markedly affected. Altered mitochondrial function, increased reactive oxygen species production, and limited protein oxidative damage were observed in advanced disease. Tau oligomers were only present in P301S mice, they were found in somatosensory cortex and hippocampi at the age of 3 months, and they increased across time in the somatosensory cortex and were higher and sustained in hippocampi. Age-related modifications in lipid composition occurred in both P301S and wild-type mice with regional and phenotypic differences; however, changes of total lipids did not seem to have pathogenic implications. Apoptosis only occurred in restricted regions in late disease. The complex tau pathology, mitochondrial alterations, oxidative stress damage, glial reactions, neuroinflammation, and cell death in P301S mice likely parallel those in FTLD-tau. Thus, therapies should focus first on abnormal tau rather than secondary events that appear late in the course of FTLD-tau. Abstract : Supplemental Digital Content is available in the text.